2007
DOI: 10.3201/eid1304.061501
|View full text |Cite
|
Sign up to set email alerts
|

Human Bocavirus, a Respiratory and Enteric Virus

Abstract: In Spain, human bocavirus (HBoV) was detected in 48 (9.1%) of 527 children with gastroenteritis at similar frequency as for children with respiratory illness (40/520, 7.7%). Fecal excretion adds new concern about the transmission of HBoV. To our knowledge, this report is the first to document HBoV in human feces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
174
3
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(214 citation statements)
references
References 7 publications
17
174
3
20
Order By: Relevance
“…In this study, a detection rate of 5.8% was observed for HBoV-1 or HBoV-3, which was similar to that reported by other studies conducted in different parts of the world , Vicente et al 2007, including Brazil (Albuquerque et al 2007). Based on the mean occurrence of other gastroenteric viruses in the region, HBoV-1 could be considered the third most common after RVAs and human cali-civiruses (Cardoso et al 2003, Costa et al 2004, Borges et al 2006, Andreasi et al 2008.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, a detection rate of 5.8% was observed for HBoV-1 or HBoV-3, which was similar to that reported by other studies conducted in different parts of the world , Vicente et al 2007, including Brazil (Albuquerque et al 2007). Based on the mean occurrence of other gastroenteric viruses in the region, HBoV-1 could be considered the third most common after RVAs and human cali-civiruses (Cardoso et al 2003, Costa et al 2004, Borges et al 2006, Andreasi et al 2008.…”
Section: Discussionsupporting
confidence: 91%
“…HBoV detection in faecal samples from individuals with acute gastroenteritis has gained importance following the positive identification of bocavirus in faecal samples from individuals throughout the world (Albuquerque et al 2007, Lau et al 2007, Monteny et al 2007, Vicente et al 2007, Han et al 2009, Chow et al 2010, Kantola et al 2010, Jin et al 2011. In Brazil, only three studies have been published regarding HBoV detection in children with acute gastroenteritis (Albuquerque et al 2007, Santos et al 2010, Proença-Modena et al 2011 and this is the first study conducted in the Central-West Region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Most prevalence studies were done on samples from children with respiratory tract diseases, with rates observed between 1.5-19% (1,(4)(5)(6)(7)(8)(9)(10)(11)(12). Studies made on fecal specimens indicate that HBoV is also prevalent in children with acute gastroenteritis, with 0.8-16% of samples being HBoV + (4,(13)(14)(15). In addition, HBoV infection with complex clinical conditions in immunosuppressed patients has been suggested (16).…”
mentioning
confidence: 99%
“…Three other strains of hBoV were discovered in 2010 and are now referred to as hBoV2, hBoV3 and hBoV4 [37][38][39]. HBoV1 causes respiratory diseases and is present everywhere across the globe accounting for about 19 % of all viral infections of the upper and lower respiratory tract in humans [40][41][42]. HBoV1 effectively infects epithelial cells of human airways and induces their cytolysis [43][44][45].…”
Section: Human Bocavirusmentioning
confidence: 99%